Academics and intellectual honesty - Abdul Razak, Dzulkifli (The Sun, 2019)
IN academic circles, intellectual honesty is deemed a prized item as this is what defines knowledge, the way it is generated and disseminated. Knowledge is debated and scrutinised publicly to ensure that the highest level of honesty is maintained. It is open to all forms of critique by just about anyone interested in the subject. This is a safeguard against any devious agenda held by vested interest groups in promoting the so-called knowledge in the interest of many.